Insights Into Oxidized Lipid Modification in Barley Roots as an Adaptation Mechanism to Salinity Stress - Yu, Dingyi; Boughton, Berin A.; Hill, Camilla B.; Feussner, Ivo; Roessner, Ute; Rupasinghe, Thusitha W. T. (Frontiers in Plant Science, 2020)
Lipidomics is an emerging technology, which aims at the global characterisation and quantification of lipids within biological matrices including biofluids, cells, whole organs and tissues. The changes in individual lipid molecular species in stress treated plant species and different cultivars can indicate the functions of genes affecting lipid metabolism or lipid signalling. Mass spectrometry-based lipid profiling has been used to track the changes of lipid levels and related metabolites in response to salinity stress. We have developed a comprehensive lipidomics platform for the identification and direct qualification and/or quantification of individual lipid species, including oxidized lipids, which enables a more systematic investigation of peroxidation of individual lipid species in barley roots under salinity stress. This new lipidomics approach has improved with an advantage of analysing the composition of acyl chains at the molecular level, which facilitates to profile precisely the 18:3- containing diacyl-glycerophosphates and allowed individual comparison of lipids across varieties. Our findings revealed a general decrease in most of the galactolipids in plastid membranes, and an increase of glycerophospholipids and acylated steryl glycosides, which indicate that plastidial and extraplastidial membranes in barley roots ubiquitously tend to form a hexagonal II (HII) phase under salinity stress. In addition, salt-tolerant and salt-sensitive cultivars showed contrasting changes in the levels of oxidized membrane lipids. These results support the hypothesis that salt-induced oxidative damage to membrane lipids can be used as an indication of salt stress tolerance in barley.